Enhancing Infection Control Protocols Across Medical Teams: A Comprehensive Approach for Safer Healthcare - Alghfainah, Mohamed Abdullah Mosleh; Al Abbas, Ali Mohammed Hussain; Alabbas, Abdullah Mohammed Hussain; Al Abbas, Hussain Mohammed Hussain; al munyif, Kudaysi Mana salem; AL MUNEEF, ABDULLAH MANA SALEM; Sager, Jahweel Saad Hadi; Sager, Mohammed Saad Hadi; sagar, Saleh saad Hadi; Al Abbas, Saleh Mohammed Hussain (Journal of Ecohumanism, 2024)
Healthcare-associated infections (HAIs) pose significant risks to patient safety and healthcare quality, impacting all levels of medical staff. This article examines the development and implementation of enhanced infection control protocols aimed at reducing infection rates through a unified, multidisciplinary approach. By engaging healthcare providers across roles—including physicians, nurses, support staff, and administrators—we identify key factors affecting protocol adherence and infection control effectiveness. Through a mixed-methods study, we assess quantitative reductions in infection rates alongside qualitative feedback on protocol practicality and ease of use. Results indicate that comprehensive, role-specific infection control measures, paired with continuous training and feedback mechanisms, significantly improve adherence and reduce HAIs. This study underscores the value of adaptable, universally applied protocols to establish safer healthcare environments, advocating for further research and sustained implementation efforts in diverse clinical settings.